Assessment of electroencephalogram-based quantium nociception and quantium consciousness indices for intraoperative nociception and depth of hypnosis: An observational study - Deepak Sharma; Jyotirmoy Das; Sangeeta Khanna; Yatin Mehta (The Indian Anaesthetists' Forum)
Background: Intraoperative monitoring of the depth of nociception is important and often challenging. Adequacy of analgesia is essential for controlling stress response, central sensitization, and development of postoperative acute and chronic pain syndrome. The recently introduced CONOX® monitor (Quantium Medical, Barcelona, Spain) measures the quantium consciousness (qCON) index as the measure of depth of anesthesia and quantium nociception (qNOX) index as a measure of the probability of response to noxious stimuli based on patient’s electroencephalographic data. In our study, we evaluated the reliability of nociception predictability of the qNOX index and compared the reliability and sensitivity of qCON with the standard bispectral index (BIS) monitor for depth of hypnosis. Aim: The primary objective of our study was to evaluate whether qNOX can reliably predict patient movement in response to noxious stimuli. As a secondary objective, we compared qCON with BIS for monitoring hypnosis and to assess the responsiveness of qCON monitor to BIS monitor for the changing levels of hypnosis. Setting and Design: The prospective, observational, and comparative study was conducted at Medanta the Medicity Hospital, Gurugram. Methodology: This prospective and observational study was conducted at Medanta the Medicity Hospital after Institutional review board approval and informed written consent. Sixty-four patients of ASA physical status I or II scheduled for day care surgery under general anesthesia without muscle relaxant were enrolled for the study. Values of BIS, qCON, and qNOX were recorded preinduction, at the time of loss of response to verbal command after induction, at laryngeal mask airway supraglottic airway device (SGD) insertion and at the time of skin incision/surgical stimulus. Patient’s movement was noted at the time of SGD insertion and skin incision/surgical stimuli as patients were categorized into “movers” and “nonmovers.” Statistical Analysis: Data collected were analyzed with quantitative parameters expressed as mean and standard deviation. Categorical data were expressed as absolute number and percentage. Cross tables generated and Chi-square test was used for testing of associations. P < 0.05 was considered statistically significant. Results and Observations: We observed that overall sensitivity and specificity of qNOX were 37.04% and 86.14%, respectively. Positive predictive value and negative predictive value of qNOX were 41.67% and 83.65%, respectively. The accuracy of qNOX was 75.78%. There was a good positive correlation between BIS and qCON at different observational time points. Conclusion: qNOX index is a reliable predictor of patient’s depth of nociception. qCON is comparable to BIS for the depth of anesthesia monitoring.